Instilling Tasâmuh Values in Shaping Children's Personalities at Harapan Mulia Orphanage - Raihanah, Raihanah; Rahmah, Rahmah; Ain, Hafizah Qurratul (Universitas Wahid Hasyim Semarang, 2024)
This research aims to find out how the instillation of tasâmuh values in shaping the personality of foster children, as well as identifying supporting and inhibiting factors in the implementation of instilling tasâmuh values in shaping the personalities of foster children at the Harapan Mulia Marabahan Orphanage. The type of research used is field research with a descriptive approach. The research subjects consisted of caregivers, administrators and foster children. Meanwhile, the object of this research is instilling the value of tasâmuh in foster children as well as supporting and inhibiting factors in instilling the value of tasâmuh in foster children at the Harapan Mulia Marabahan Orphanage. Based on the data findings, it was found that instilling the value of tasâmuh in shaping the personality of foster children was carried out in several ways, namely through orphanage regulations, such as routine activities, rules, sanctions and punishments. Meanwhile, what caregivers apply is advice and examples. The supporting factors for instilling tasâmuh values are the small number of foster children and a positive response from the local community/government, the inhibiting factors are those that come from the environment outside the orphanage which concerns the child's interactions and the child's life before joining the orphanage which has a different parenting pattern in the orphanage.